Application of QFD methodology in the development of support used in racing drones made through additive manufacturing - Chixaro, Davi; Drozda, Fabiano; Silva, Ricardo (Brazilian Journal of Production Engineering, 2024)
The drone industry has been growing, especially in the racing drone niche, often built using modular parts following the "do it yourself" (DIY) concept. This article explores the use of a methodology for defining customer criteria, Quality Function Deployment (QFD), presenting its application in the development of a product manufactured by Fused Deposition Modeling (FDM) for a GoPro® camera mount on racing drones. 3D printers are widely used due to their speed and ease of use, especially in the rapid prototyping of parts. Applying QFD to build a prototype of an action camera mount for racing drones that meets customer demands, subsequently manufactured by 3D printing, and evaluating pre-established parameters. The results met the pre-established QFD parameters, especially the v03 prototype, which achieved the best results. The tool was particularly useful in defining which criteria would be studied and how they would be applied in the product development process.
Keywords: Fused Deposition Modeling; Quality Function Deployment; Additive Manufacturing; Product Design